PENGARUH SERVQUAL, HARGA DAN CUSTUMER EXPERIENCE TERHADAP KEPUASAN PELANGGAN COFFEE SHOP HDS: Service Quality, Price, Customer Experience, Customer Satisfaction - Della Septiana; Meisa Fitri Nasution (BJRM (Bongaya Journal of Research in Management), 2026)
Customer satisfaction is of utmost importance for businesses operating in the food service industry amid today’s increasingly intense business competition. One strategic advantage for businesses regarding the importance of maintaining customer satisfaction is the long-term and cumulative benefits it yields. The purpose of this study is to determine the partial and combined effects of service quality, price, and customer experience on customer satisfaction at HDS Coffee Shop. This study is a quantitative descriptive research using a sample of 100 customers of Coffee Shop HDS in Cikampak, South Labuhanbatu Regency. Multiple linear regression analysis was employed for data analysis. The conclusion of this study is that the profile of respondents who are customers of Coffee Shop HDS consists of male customers belonging to Generation Z. The results indicate that service quality influences customer satisfaction; the price variable has a positive and significant effect on customer satisfaction; the customer experience variable influences customer satisfaction; and service quality, price, and customer experience collectively influence customer satisfaction